Aspettative e narrazioni: spunti per una riflessione interdisciplinare - Andrea Declich (Quaderni di Sociologia, 2014)
The article is a reflection on the formation of expectations. A brief presentation of the main concepts of expectations in economics and sociology is presented and, on the basis of some considerations concerning the debate in economics, some issues related to expectations are raised that demonstrate the utility and urgency of dealing with this issue, also in an interdisciplinary perspective (for example, innovation or the need to manage expectations in the framework of public policies). On these bases, the strong connection between expectations and narrative (storytelling) – emerging from the work of some sociologists and economists, although not systematically – is dealt with. Finally, and based on this connection, some issues are singled out that are considered worthy of further inquiry.